FIVE-YEAR DYNAMICS OF CIRCADIAN BLOOD PRESSURE PROFILE IN FAR NORTH WORKERS WITH ARTERIAL HYPERTENSION - I. L. Zapesochnaya; A. G. Avtandilov (Российский кардиологический журнал, 2013)
Aim. In a prospective study, to assess the dynamics of circadian profiles of blood pressure (BP) in Far North workers with arterial hypertension (AH) and different shift working patterns. Material and methods. In the first phase of the study (2003–2005), 95 patients with Stage 1–2 AH were examined. Group I included 53 patients who worked only day shifts; Group II included 42 patients who worked alternating day and night shifts. In the second phase (2007–2011), both groups were examined, including 24-hour BP monitoring, and two subgoups (treated vs. untreated AH) were defined. Results. In Far North workers with AH, there was a negative dynamics in circadian BP profile, particularly among night shift workers. AH patients require antihypertensive combination therapy irrespective of their shift working patterns.